A STUDY ON THE IMPLEMENTATION OF ENGLISH SCHOOL BASED CURRICULUM IN SMA NEGERI 5 DENPASAR - Widiastuti, I.A.Md.Sri; Padmadewi, Ni Nym; Artini, L.P. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
Abstract   This research was conducted in an attempt to analyze and describe the implementation of English School Based Curriculum (ESBC) in SMAN 5 Denpasar in the academic year 2012/2013.The setting of the research was in three classes and there were three teachers as the subjects of the study. The primary reasons for taking this school as the research setting was mainly because this school provides learners with National as well as International Standard. The teaching and learning processes were conducted entirely in English and the ESBC has been implemented since 2006.The sources of the data were Syllabus, lesson plans and the teaching and learning activities in naturalistic environment of the classroom. This research was conducted to figure out the teachers? understanding of ESBC, the planning of ESBC, the implementation of ESBC and the teachers? problems in implementing ESBC. This study revealed that the teachers under study needs to improve their understanding of ESBC, their ability in designing English syllabus and lesson plan as well as their ability in implementing ESBC in more contextualized learning activities.   Key Words: English School Based Curriculum, National Standard of Education, International Standard of Education